The Development of Firm Value Model on Tax Avoidance Activities of Consumer Goods Industry During COVID-19 Pandemic - Nita Rosadiya; Ni Putu Eka Widiastuti; Sri Mulyantini (Syntax Corporation Indonesia, 2022)
This study aims to analyze the influence between the implementation of Good Corporate Governance, Financial Leverage, and risk management on company value through Tax Avoidance in the Consumer Goods Industry during the Covid-19 pandemic. The research methodology uses case study quantitative methods. The research sample is 70 consumer goods industries listed on the IDX, which have released their financial statements for the 2019-2020 period. The total sample data is 140 data that will be observed. The data analysis technique uses Path Analysis with E-views and Microsoft Excel 2019. The current research results show that the GCG (X1), Financial Leverage (X2), and Risk Management (X3) variables have a significant effect on Firm Value (Y). at the same time, the Tax Avoidance variable cannot moderate the relationship between GCG and Risk Management on Company Value. However, the Tax Avoidance variable can moderate the relationship between Financial Leverage and Firm Value.